Random dithienosilole-based terpolymers: Synthesis and application in polymer solar cells. (July 2016) - Liu, Lijie; Zhang, Lipeng; Li, Miao; Guo, Yijing; Song, Jinsheng; Wang, Hua
Abstract: A series of random dithienosilole-based terpolymers are prepared from two different dithienosilole monomers with nonanoyl group and malononitrile as the electron withdrawing groups via microwave assisted Stille coupling polymerization. The chemical structures of the final terpolymers are confirmed by the 1 H NMR and all polymers present good thermal stability. With the elevated ratios of the nonanoyl group modified dithienosilole, the intramolecular charge transfer peaks are redshifted and the highest occupied molecular orbital energy levels are increased gradually. These polymers are also tried as the donor materials for polymer solar cells and all polymers presented high open-circuit voltage above 1.0 V. The final power conversion efficiencies are ranged from 1.16% to 3.29% with the tuned ratios of the monomers. Graphical abstract: Highlights: Two asymmetrical dithienosilole building blocks are utilized. A series of dithienosilole based conjugated terpolymers are prepared. Uv–vis absorption and HOMO levels could be tuned. Monomer feeding ratios play important roles in ICT and photovoltaic performance.